The Role of Implementation New Technologies in Medium-Sized Enterprises in Selected Regions - Madzinová, Renáta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The segment – Small and medium sized enterprises, plays the biggest role in every economy. The situation is different when considering the penetration of SMEs in international markets. The worst state of affairs is in developing and implementing the latest technologies into business practice. The article deals with the influence of new technology on SMEs operation and penetration of medium-sized enterprises in international markets. The conclusion provides recommendations on how to increase the competitiveness of medium-sized businesses in international markets.

Największą rolę w każdej gospodarce odgrywa segment małych i średnich przedsiębiorstw. Sytuacja ulega zmianie, gdy mówimy o rozpowszechnieniu MŚP na rynkach międzynarodowych. Najsłabiej jest w opracowywaniu i wdrażaniu najnowszych technologii do praktyki gospodarczej. Artykuł dotyczy wpływu nowej technologii na działalność małych i średnich przedsiębiorstw, jak i rozpowszechnieniu średnich przedsiębiorstw na rynkach międzynarodowych. W podsumowaniu zamieszczono zalecenia, jak zwiększyć konkurencyjność średnich przedsiębiorstw na rynkach międzynarodowych.
Keywords: medium-sized entrepreneurship; international markets; presov region; region of Podkarpatie in Poland; technology; przedsiębiorczość średniej wielkości przedsiębiorstw; rynki międzynarodowe; region Presov; Podkarpacie; technologia